Gardening with Annuals in Florida - Sydney Park Brown (EDIS)
Annuals offer an almost infinite variety of flower color and plant form. They brighten landscape beds and add a splash of color to a porch, deck, or patio when placed in containers. Some also make good cut flowers. This revised 6-page fact sheet was written by Sydney Park Brown and published by the UF Department of Environmental Horticulture, August 2014.